MIGRANT WORKERS: A RISK FACTOR FOR HIV TRANSMISSION - Ikram, Nadeem; Kamal, Qazi Mujtaba; Ahmed, Sabina Nisar; Hassan, Mehmood ul; Tariq, Hayat Mir (Journal of Ayub Medical College Abbottabad, 2011)
Background: HIV continues to be a threat in both developed and developing countries. Pakistan has entered concentrated epidemic from low epidemic stage. The prevalence of HIV is more in at risk population particularly intravenous drug users (IDUs). Studies are required to find out other risk factors contributing to spread of the disease in the general population in order to prevent the spread of disease among general population. Methods: A cross-sectional study was carried out on patients reporting for HIV testing at National HIV/STI Referral Lab, National AIDS Control Program (NACP) from January to December 2011. Results: A total of 345 patients reported to the lab during the study period. The detailed histories of 271 patients were available out of which 131 (48.3%) patients were found to be positive for HIV. Minimum age of patient with HIV was 2 years while maximum age was 64 years. HIV affected those more significantly who had visited abroad (p=0.000) or were IDUs (p=0.000). Extramarital sexual activity, blood transfusion, or any surgical procedure in the past was not found to be significant (p=0.574, p=0.243, p=0.252 respectively). Most of the affected males were drivers (16, 12.2%) by profession. Among them 9 had visited gulf countries and 4 of them were deported from the gulf countries having HIV. Conclusion: Migrant workers are a risk factor for HIV transmission. Policy may be developed to focus on this population who continues to spread HIV among their spouses and children as a result of unawareness about their HIV status and its modes of transmission. Keywords: Migrant workers, HIV, gulf countries, deported